Impact of cannabis abuse on the occurrence of stroke in young people: a systematic review and meta-analysis - Liu, Dongxue; Yang, Liu; Liu, Peiqi; Wang, Yujiao; Gao, Lan (Frontiers in Neurology, 2024)
Background The occurrence of stroke in young people has risen significantly. This can easily lead to physical disabilities, swallowing difficulties, and cognitive impairment, among other issues, having a profound impact on families and society. Risk factors for stroke in young people differ from those for traditional stroke, with cannabis abuse emerging as a significant high-risk factor. However, the extent of the impact of cannabis abuse on the occurrence of stroke and the rate of disability in young people remains unclear. To clarify this issue and provide evidence supporting the primary prevention of stroke in young people, this systematic review and meta-analysis summarizes the latest findings from previous studies. Methods A systematic search of PubMed, EMBASE, Cochrane Library, and Web of Science databases was conducted until April 2023. The review included observational studies comparing stroke risk estimates between cannabis abusers and non-users. Results This review included six observational studies focusing on cannabis abuse, involving 119,284,152 participants. A significant association was found between cannabis abuse and an increased risk of stroke [OR = 1.14, 95% CI (1.08, 1.20)]. However, there was substantial heterogeneity among the studies (I2 = 89%, p < 0.001). After adjusting for confounders such as smoking and alcohol abuse, we found a stronger association between cannabis abuse and stroke in young adults [OR = 1.21, 95% CI (1.12, 1.29)]. Subgroup analyses revealed no significant difference in stroke risk between ischemic and hemorrhagic strokes (p = 0.43). Conclusion The results of our systematic review and meta-analysis showed that cannabis abuse has a more significant effect on the occurrence of stroke in young people; however, it was not possible to distinguish whether cannabis abuse is more likely to cause ischemic or hemorrhagic stroke. Further research is needed to explore the impact of different drug types, dosages, and behaviors on stroke risk. Systematic review registration https://www.crd.york.ac.uk/prospero/, Identifier CRD42023443261.